Position-sensitive non-destructive detection of charged-particle bunches in low-energy beamlines - Stefan Ringleb; Markus Kiffer; Jonas K. C. Ballentin; Thomas Stöhlker; Manuel Vogel (Scientific Reports, 2023)
Abstract We have developed and operated an electronic detection system for the non-destructive single-pass detection of bunches of charged particles in a beamline that allows for a measurement of their lateral position with respect to the central beamline axis on a shot-to-shot basis. It provides all features of our related development reported in Kiffer et al. (Rev Sci Instrum 90:113301, 2019), namely single-pass measurement of bunch length, kinetic energy and absolute charge, and is additionally designed to provide the lateral position of bunches with sub-mm accuracy. We show the setup, associated methods and provide characterizing measurements with bunches of highly charged ions in the keV regime of kinetic energy that demonstrate the capabilities and show a typical application.